Managing China's rise in the Indo-Pacific: Japan's strategic engagement with India. (3rd July 2021) - Kaura, Vinay; Kumawat, Garima
ABSTRACT : The article explains how Japan's strategic interests are converging with India against an assertive China in the Indo-Pacific. Japan has been pursuing a "Free and Open Indo-Pacific" (FOIP) policy, which seeks to manage China's rise by deepening Japan's strategic coordination and cooperation with its closest partners through the Quad. Though Japan still values its bilateral relationship with the United States (US), its security partnership with India is part of Tokyo's persistent efforts to support the US-led rules-based international order. In order to counter China's Belt and Road Initiative (BRI) in the Indo-Pacific region, Japan has been a strong supporter among the Quad to promote non-military cooperation, primarily focusing on infrastructure building, supply chain resilience and technological innovations. The article argues that Japan's strategic engagement with India is now an integral part of its wider national security posture as Tokyo has come to recognise New Delhi as an important balancer against Beijing. That the US has enhanced its ties with India in recent years has further facilitated Japan–India strategic convergence since it is aligned with American policy towards the Indo-Pacific region in an era of great power competition.